Universities and values in a global context - León García, Fernando (My University, 2024)
the values that universities promote and embody are crucial for navigating the complex challenges of today’s world. Universities must reflect on and reinforce their core values in all aspects of their operation, ensuring they remain places of respect, openness, and critical thought. By doing so, they not only educate individuals but also contribute to the broader goal of creating a more informed, tolerant, and just society. As Fanta Aw (International Educator, January 10, 2024) has stressed “...the antidote to war and polarization is increasing intercultural competence, demonstrating compassion, and combatting hate. Our work is more important than ever, for if done at scale and in sustained ways, it serves as a path to a more interconnected, peaceful world. The ability to know the “other” and understand with head and heart that the “other” is us and we are the “other” is vital to our existence and ability to thrive in an interdependent world.”
IAU Horizons
Keywords: Universities; Values; Campus Mexicali